Notes on Revolution and the Southern Question: Gramsci with Lenin - Chiesa, Lorenzo (Stasis, 2018)
In this article I argue that Gramsci’s answer to the so-called Southern Question is a proletarian revolution and the creation of a proletarian state in Italy that closely follow the Bolshevik model. I aim at showing that Gramsci’s stance is therefore unequivocally Leninist and can be correctly understood only by means of an analysis of Lenin’s own stance on the role of the peasantry in the socialist revolution and the ensuing dictatorship of the proletariat. I further claim that Gramsci’s Leninism has been repressed in academic debates, especially in the context of post-colonial and subaltern studies, and that the latter would benefit from considering the way in which Lenin treats the relation between the proletarian revolution/state and the “oppressed people” of the world at large.